What is the future of patient reported outcomes in sickle cell disease? - Singh, Sharon A. (Expert Rev Hematol, 2020)
INTRODUCTION: Sickle cell disease (SCD) is a complex, chronic disease caused by abnormal polymerization of hemoglobin, which leads to severe pain episodes, fatigue, and end-organ damage. Patient reported outcomes (PROs) have emerged as a critical tool for measuring SCD disease severity and response to treatment. AREAS COVERED: Authors review the key issues involved when deciding to use a PRO in a clinical trial. We describe the most highly recommended generic and disease-specific PRO tools in SCD and discuss the challenges of incorporating them in clinical practice. EXPERT OPINION: PRO measures are essential to incorporate into SCD clinical trials either as primary or secondary outcomes. The use of PRO measures in SCD facilitates a patient-centered approach, which is likely to lead to improved outcomes. Significant challenges remain in adapting PRO tools to routine clinical use and in developing countries.